Comparative Study of Staples vs Plate and Screws for Arthrodesis of the First Metatarsophalangeal Joint - Rebecca S. McGaver MS, ATC; Ahmed Khalil Attia MD; Kayla J. Seiffert BA; Carissa Dock BBME; Jeffrey D. Seybold MD; Paul M. Cammack MD (Foot & Ankle Orthopaedics)
Category: Midfoot/Forefoot; Other Introduction/Purpose: Nitinol technology has revolutionized foot and ankle orthopaedic surgery, offering a quick and low-profile means of achieving bone healing. One application of this technology has been in the development of a first metatarsophalangeal (MTP) joint staple, utilized in place of crossing screws or a plate and interlocking screws constructs to achieve fusion at the first MTP joint. The objectives of this study were to compare radiographically and subjective outcomes for patients who had a first MTP joint fusion treated with an Enovis Dynaclip Delta staple vs those treated with a plate and interlocking screws. The hypothesis is the staple provides a quicker surgical time and equivalent rate of union compared to patients who were treated with standard plate and screws. Methods: A single-surgeon, consecutive case series of prospectively collected data was reviewed retrospectively for patients who underwent primary first MTP arthrodesis using a staple. Patients were age and gender matched to those who underwent primary first MTP arthrodesis with a plate and associated interlocking screws. Dates of surgery were November 2017 - December 2023. Exclusions included revision surgeries, prior forefoot/midfoot fusions, and ancillary fusions at the time of the index surgery. Preoperative and postoperative patient-reported outcome measures (PROMs) [Foot and Ankle Ability Measure (FAAM), Veterans-Rand 12 (VR-12) General Health Survey, visual analog pain scale (VAS), and radiographs (hallux valgus angle, dorsiflexion angle) were evaluated to compare the two groups. Comorbidities, operative time, fusion rates, and a patient satisfaction survey were also collected. Statistical analysis was performed using sutdent’s t-tests. Results: Twenty-two feet were included in both groups. Preoperative and postoperative PROMs between groups demonstrated no significant differences in all questionnaire categories assessed. The staple group demonstrated significant differences from preoperative to postoperative in FAAM ADL (p=0.004), FAAM sport (p=0.010), and VAS (p< 0.001) while plate and screws demonstrated significant differences in FAAM ADL (p=0.032) and VAS (p=0.033). The radiographic measurements revealed a significant difference in the postoperative dorsiflexion angle for staple vs plate and screws 21.81±5.72 vs 26.47±6.99, respectively (p=0.012) and there were no other significant differences noted (table). Operative time revealed a significant difference between staple vs plate and screws (30.0 minutes vs 35.73 minutes, respectively) (p=0.006). The fusion rate was 95% in both groups. Conclusion: This study reports early results for a comparison of first MTP joint fusion treated with an Enovis Dynaclip Delta staple vs those treated with the standard plate and interlocking screws. While there were statistical differences within each group between most of the preoperative and postoperative PROMs, comparing the two groups, there was none. The fusion rate was the same in both groups. The staple group had an average of 5.7 minutes less operative time. Staple fixation achieves similar union rates to plate and screw constructs with a shorter operative time. Further patients are needed to expand this cohort.